Characterization of spiced and malted maize supplemented orange-fleshed sweet potato beverage - Oyedokun, James; Olaoye, B M; Ade Omowaye, B I O (Bangladesh Journal of Scientific and Industrial Research, 2025)
Beverages made with spiced and malted maize (MM) and orange-fleshed sweet potato were characterized. The beverages were formulated by gradually adding 5 g of MM, ranging from 0 to 25 g, to OFSP extract containing a ginger-garlic (G-G) mixture and sugar. The samples were pasteurized, evaluated, and monitored for microbiological qualities for four weeks, after which the data were statistically assessed. With the exception of specific gravity and vitamin C, all physicochemical attributes increased as MM increased. The color and general acceptance evaluations of the beverages were improved with an increase in MM up to 20 g. Since G-G-spiced OFSP beverages containing 10, 15, and 20 g of MM demonstrated beneficial qualities, they may be added to the existing health-promoting beverages. Bangladesh J. Sci. Ind. Res. 60(1), 35-44, 2025